Sukcesija na prodiščih reke Save - Geršič, Matjaž (Dela - Oddelek za geografijo Filozofske fakultete v Ljubljani, 2010)
This article presents a biogeographic analysis of vegetation on point bars. The results are based primarily on an analysis of off-road mapping, which was conducted in nine selected point bars of the upper stream of the Sava River. Human interference and functional significance of point bars have been researched, too. As a result of our research a graphic model of succession on the point bars has been created.
Keywords: biogeografija; biogeography; fizična geografija; Gorenjska; habitati; physical geography; prodišča; rastlinstvo; Sava; Slovenia; Slovenija; Upper Carniola